2022
DOI: 10.1111/pce.14337
|View full text |Cite
|
Sign up to set email alerts
|

Multienvironment QTL analysis delineates a major locus associated with homoeologous exchanges for water‐use efficiency and seed yield in canola

Abstract: Canola varieties exhibit variation in drought avoidance and drought escape traits, reflecting adaptation to water‐deficit environments. Our understanding of underlying genes and their interaction across environments in improving crop productivity is limited. A doubled haploid population was analysed to identify quantitative trait loci (QTL) associated with water‐use efficiency (WUE) related traits. High WUE in the vegetative phase was associated with low seed yield. Based on the resequenced parental genome dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 84 publications
(129 reference statements)
2
21
0
Order By: Relevance
“…Multi-environment studies can be more powerful in detecting smaller effect quantitative trait loci (QTL) controlling complex traits such as yield, allowing for the identification of QTL of pleiotropic effect or QTL that suffer significant effects due to GxE interaction [ 54 , 56 , 57 ]. For instance, a study using segregating B. napus populations showed that 81.5% of the QTL linked to yield were pleiotropic [ 58 ]. In B. napus , a multi-environment analysis of seed composition traits observed that most QTL suffered from GxE effects, with a major QTL qWIE_N9 associated with seed pigment in over five environments [ 56 ].…”
Section: Bridging the Genetic And Phenotypic Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…Multi-environment studies can be more powerful in detecting smaller effect quantitative trait loci (QTL) controlling complex traits such as yield, allowing for the identification of QTL of pleiotropic effect or QTL that suffer significant effects due to GxE interaction [ 54 , 56 , 57 ]. For instance, a study using segregating B. napus populations showed that 81.5% of the QTL linked to yield were pleiotropic [ 58 ]. In B. napus , a multi-environment analysis of seed composition traits observed that most QTL suffered from GxE effects, with a major QTL qWIE_N9 associated with seed pigment in over five environments [ 56 ].…”
Section: Bridging the Genetic And Phenotypic Gapmentioning
confidence: 99%
“…In B. napus , a multi-environment analysis of seed composition traits observed that most QTL suffered from GxE effects, with a major QTL qWIE_N9 associated with seed pigment in over five environments [ 56 ]. Another study identified a QTL region on chromosome A09 linked to variation in days to flowering, seed yield and plant height under water limited conditions [ 58 ]. However, measuring phenotypic traits of hundreds of plants growing in multiple location breeding trials is costly and time consuming, restricting the number of traits measured and frequency of measurements through crop development.…”
Section: Bridging the Genetic And Phenotypic Gapmentioning
confidence: 99%
“…Drought avoidance traits such as leaf carbon isotope discrimination (Δ 13 C) and root traits (root pulling force, root length and root biomass) enable plants to maintain water status at a high vapour pressure deficit and were associated with improved water use efficiency (WUE) and seed yield in canola. Many quantitative trait loci (QTL) underlying variation for drought escape traits, seed yield and drought avoidance traits have been detected in canola [ 13 , 14 , 15 , 16 ]. However, few studies have reported QTL and correlated phenotypes for response to water stress under contrasting rainfed (DRY) and irrigated (WET) environments in canola [ 11 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both parental lines showed a negative relationship with Δ 13 C and i WUE, measured as a ratio between light-saturated assimilation rate ( A ) and stomatal conductance to the diffusion of water vapour ( g sw ) [ 20 ]. In the doubled haploid (DH) population derived from BC1329/BC9102, Raman et al [ 15 ] reported a total of 29 QTL (15 QTL for main effects—corresponding to genotypic (G) effects—and 14 for QTL (Q) by Environment (E) interactions (QE)—corresponding to genotype by environment (GE) effects for variation in drought avoidance traits—Δ 13 C, early vigour, and plant height and drought escape traits such as flowering time in canola under field and shade-house conditions). However, the relevance of those QTL and phenotypic correlations between yield-related traits in contrasting water regimes was not detailed in the complete set of DH lines derived from BC1329 and BC9102.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation